The Poetry and Prose of Wang Wei Volume I - Rouzer, Paul (Library of Chinese Humanities, 2020)
Wang Wei has traditionally been considered one of the greatest of Tang dynasty poets, together with Li Bo and Du Fu. This is the first complete translation into English of all of his poems, and also the first substantial translation of a selection of his prose writings. For the first time, readers encountering his work in English translation will get a comprehensive understanding of Wang Wei's range as a poet and prose writer.